Analyzing the curriculum - Posner, George J. (McGraw-Hill, 2004)
This book can provide the backbone for a basic curriculum course; as a supplemental text, it can be used alongside a more comprehensive text as a means of helping students apply their knowledge to a particular case study. This book teaches the student how the parts of curriculum fit together and how to identify assumptions underlying curricula.